OPTIMALISASI AUDIT INTERNAL: IMPLEMENTASI DAN MANFAAT PROSES VOUCHING - Rizqi Fahmi Fadillah; Erna Sulistyo (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
. Internal audit is a method of internal control over all activities within the company. This article was prepared to determine the optimization of internal audit regarding the implementation and benefits of the vouching process. This article was prepared using descriptive qualitative methods. This research was carried out by looking at and observing every supporting document owned by PT X. The results of this research show that the internal audit at PT. X has been carried out optimally through the implementation and benefits of vouching. Optimizing internal audits can be done through vouching. Vouching provides benefits related to the verification process between conformity or indications of fraud that can be identified by the auditor. This optimization can increase efficiency and accuracy in the audit process. Apart from that, having appropriate vouching can help increase the trust of every user of financial statements.